Pengaruh Lama Penyimpanan Darah terhadap Kualitas Darah Packed Red Cell (PRC) di UTD RSUD Kabupaten LombokUtara - Adawiyah, Luluil; Jiwintarum, Yunan; Resnhaleksmana, Ersandhi; Urip (Journal of Indonesia Laboratory Students (JILTS), 2025)
Background: Packed Red Cell (PRC) is the most widely used blood component in transfusion. In general, PRC is used for patients with anemia that is not accompanied by a decrease in blood volume, such as patients with hemolytic, acute leukemia, chronic leukemia, thalassemia, and chronic renal failure. The quality of the PRC component is done by checking the hemoglobin and hematocrit levels in the blood component products produced. In transfused blood storage there are elements of blood storage lesions including: morphological changes, slowing metabolism with decreased adenosine triphosphate (ATP) concentration, acidosis with decreased 2,3 diphosphoglycerate (2,3-DPG) concentration. This will pose a risk to the safety and efficacy of long-stored PRC.. Research Objectives: Knowing the Effect of Blood Storage Duration on the Quality of Packed Red Cell (PRC) Blood in the Blood Transfusion Unit of North Lombok Regency Hospital. Research Methods: This research is a pre-experimen The study population was all PRC blood in the Blood Transfusion Unit of NorthLombok District Hospital. The sample used was PRC blood taken randomly with a total of 24 experimental units. Using primary data and statistically analyzed with Kruskal-Wallis test. The Results: The average hemoglobin level on day 21 storage was 50.3 g/unit, day 28 was 48.8 g/unit, and on day 35 was 47.1 g/unit. The average hematocrit value on day 21 of storage was 65.6%, day 28 was 63.6%, and on day 35 was 61.4%. The results of the PRC blood quality assessment showed that on day 21 storage the blood quality was good, while on day28 and day 35 storage the PRC blood quality was not good. Effect of bloodstorage duration on PRC blood quality (p = 0.000 < α = 0.05). Conclusion: There is an effect of storage duration on the quality of PRC blood.